Determinant Factors Work Culture and Work Climate on Team Performance in Branch of the Central Aceh Region Education Service - Teniro, Alwin (prodima@fe.uika-bogor.ac.id, 2025)
The research was conducted to determine the hypothesis test for each variable studied. The data analysis was used by multiple linear regression equations and determination coefficients, t-test, and F-test of 36 Central Aceh Regency Regional Education Office, Provincial Branch respondents. The results of the study show based on a partial test that variables X1 and X2 have a positive and significant effect on employee performance, namely the Y variable at the Central Aceh Regency Regional Branch Education Office. Meanwhile, the simultaneous test that work culture (X1) and work climate (X2) have a significant effect on employee performance at the Central Aceh Regency Regional Education Office Branch, from the t and f tests show that there is a strong relationship of independent variables to dependent variables, although the ability of independent variables to affect dependent variables is 0.723 and the rest is influenced by other variables that are not observed in this study.